FLOWCYTOMETRY IN LEPTOSPIROSIS - Galya I. Gancheva; Maria Atanasova; Tzvetan Lukanov; Penka Ilieva (Peytchinski Publishing, 2008)
Differential count of leucocytes and six lymphocyte populations and subpopulations were investigated by flow cytometry in fourteen cases with leptospirosis. Marked granulocytosis and lymphopenia were found in 100%. The percentage of the monocytes was significantly decreased (mean 6,65%; 0,7 to 14,0%; sd 5,49). Immunophenotypization of lymphocyte populations and subpopulations by flow cytometry was revealed prevalent tendencies for decreasing of the number of total T-lymphocytes, T-helpers, T-suppressors, T-helpers/T-suppressors index; increasing of the number of the activated T-lymphocytes, subpopulation of NK cells (CD3-/ CD16+56+), and B-lymphocyte. These data are suggested that cell-mediated immunity plays a role in later stages of the diseases.